2016
DOI: 10.2147/dddt.s118015
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of visual disorders induced by phosphodiesterase inhibitors in the treatment of erectile dysfunction

Abstract: AimThe aim of this review was to summarize the ocular action of the most common phosphodiesterase (PDE) inhibitors used for the treatment of erectile dysfunction and the subsequent visual disorders.MethodThis is a literature review of several important articles focusing on the pathophysiology of visual disorders induced by PDE inhibitors.ResultsPDE inhibitors have been associated with ocular side effects, including changes in color vision and light perception, blurred vision, transient alterations in electrore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…This elevated intraocular pressure might cause retinal ganglion cells apoptosis [50,51] . It was reported that PDE-5 enzyme inhibitors cause dilatation of the choroidal fenestrated capillaries and leakage of plasma rich fluid into the anterior chamber with subsequent increase in the intraocular pressure [52,53,54] . In addition, the increased intraocular pressure as well as the changes in ocular blood flow diminishes the power of retinal pigment epithelium to pump fluid from retina to choroid [55] , and this negatively affect the retinal metabolism and might contribute to the pathogenesis of retinal pigment epithelium detachment, outer limiting membrane disruption and wide separation of photoreceptors outer segments that were observed in tadalafil group of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This elevated intraocular pressure might cause retinal ganglion cells apoptosis [50,51] . It was reported that PDE-5 enzyme inhibitors cause dilatation of the choroidal fenestrated capillaries and leakage of plasma rich fluid into the anterior chamber with subsequent increase in the intraocular pressure [52,53,54] . In addition, the increased intraocular pressure as well as the changes in ocular blood flow diminishes the power of retinal pigment epithelium to pump fluid from retina to choroid [55] , and this negatively affect the retinal metabolism and might contribute to the pathogenesis of retinal pigment epithelium detachment, outer limiting membrane disruption and wide separation of photoreceptors outer segments that were observed in tadalafil group of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 15 patients using 50 mg sildenafil twice weekly for 3 months, no significant effects on best-corrected visual acuity or introaocular pressure were observed (4,5). Acute secondary effects of sildenafil include headache, heartburn, skin flush, and vision changes such as blurred vision, photophobia, and cyanopsia [i.e., blue-tinted vision; (6)]. Here, we report a case series of patients who experienced visual disturbances that persisted for more than 24 h in response to taking sildenafil.…”
Section: Introductionmentioning
confidence: 99%
“…The most experimental studies with sildenafil described a venous dilatation and an increased flow, contrary to the study of Grunwald et al, which reported no effect on retinal circulation [4 -6]. Eltony et al postulated a toxic effect of chronic treatment with sildenafil in adult male rats, whereas Moschos reported no permanent toxic effects on chorioretinal tissue in humans after sildenafil intake [7,8]. Ophthalmic adverse drug re- A preretinal hemorrhage is usually induced by Valsalva retinopathy.…”
Section: Discussionmentioning
confidence: 99%